The healthy and fit translator: a reality or a necessity? - Alcalde Peñalver, Elena; Santamaría Urbieta, Alexandra (The Interpreter and Translator Trainer, 2021)
Recent research studies in translation devote increasing attention to the pivotal role that ergonomics plays in translators' workplaces. However, there are no previous research studies that focus on how effective translators' lifestyles are and provide results on how necessary it is to improve them. The aim of this paper is to show results from a pilot qualitative research study conducted in Spain with a focus group composed of a representative from four different professional profiles from the translation industry: a part-time employee at a translation company, a full-time employee at a translation company, a freelance translator, and an intern at a translation company. The focus group followed a non-structured interview and the list of topics ranged from changes in sleeping and eating patterns and regularity of physical activity depending on the volume of work translators had, to health problems related to these variations in their daily routines. Participants' qualitative answers have shed light on the topic and have allowed us to develop a questionnaire that will be distributed internationally to compare data from different countries in a future study of a wider scope.
Keywords: ergonomics; health; eating habits; physical activity; sleeping patterns; productivity; JCR; Scopus